Peran Norma Pribadi dan Awarness of Consequnces Terhadap Proenviromental Behaviour Dalam Pengelolaan Bisnis Yang Dimoderasi Oleh Status Sosial Ekonomi - Koerniawan Hidajat; Rachmawati Rachmawati; Indri Wahyu Pramesti (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
In 2018 Jakarta produces 1,900 - 2,400 tons of plastic waste / day, the entire area produced by Jakarta is around 7000 tons of waste / day. In 2016 the big problem faced by all major cities in the world was an increase in the volume of waste. In Jakarta, the data submitted by the Head of the DKI Jakarta Sanitation Service shows that DKI Jakarta is a city with a garbage volume of 6,500 - 7,000 tons per day. In overcoming floods the Government and Penprov of DKI Jakarta have made efforts to build dams, and normalize rivers. Therefore the importance of having personal values and awareness of consequences to reduce environmental problems. The purpose of this study is to see the role of personal norms and awareness of consequences on proenvironment in managing a business that is moderated by social status. The sample used was 100 people in Jakarta who have businesses aged 20-65 years. The researcher used General Ecological Behavior (GEB) to measure pro-environment behavior, the Personal Norms Scale to measure personal norms and awareness of conscience dimensions. To test the hypothesis using multiple regression. Based on the results of the analysis conducted by researchers that personal norms play a significant role in pro-environment behavior. Personal norms are a feeling of moral obligation in acting that causes pro-environmental behavior to arise. That is, the higher the personal norm possessed by the individual, the higher the pro-environment behavior shown by the individual. Personal norms also play a significant role in economic status and Awareness of Consequences have a significant role in socio-economic status.